An Analysis in Writing Analytical Exposition at Eleventh Grade Students’ of SMAN 8 Jambi City - Nabila Millenia Zulfi; Wennyta Wennyta; Yanti Ismiyati (Universitas Batanghari Jambi, 2021)
This study focuses on the students’ ability in writing analytical exposition texts in second grade at SMAN 8 Jambi City in the academic year 2020/2021. This study aims to determine the students ability in writing analytical exposition text in terms of the structure of the analytical itself, namely Thesis, Argument, and Reiteration. The purpose of this research is to see the students’ ability in writing analytical exposition text. This research was conducted at SMAN 8 Jambi City. This research used a descriptive qualitative method by taking the sample used simple random sampling and then obtained XI IPS 2 with the total number of 36 students as subject of the research. The instrument used is writing test based on the topic that has been determined by this research. In this study this research used an assessment rubric adapted from the Hamp-Lyons theory used by a team of assessors who are experts in the field of writing. The result of this study showed the students’ ability in writing analytical exposition text were: 6 students get very good criteria, 14 students get good criteria, 10 students get adequate criteria, and 6 students get poor criteria. This means, most of the XI IPS 2 at SMA N 8 Jambi City students got “good” criteria in writing Analytical Exposition Text. Therefore, students have to pay attention to their writing skills and all criteria that must be met to make good writing.Key Words: Analytical exposition, Writing test, Writing ability.